Transforming Digital Inclusion into Algorithmic Justice in the Islamic Economy: A Systematic Literature Review from a Maqāṣid al-Sharīʿah Perspective - Muhammad Maimun Haki Al Arif; Muhammad Alfan Taufiqi; Fathimatuz Zahroh; Nur Mahmudah El Madja (Institut Nalanda, 2026)
This study aims to map the transformation of digital inclusion into algorithmic justice in the Islamic economy through the lens of Maqāṣid al-Sharīʿah. Employing a Systematic Literature Review method adapted from the PRISMA 2020 framework, this study examines literature published between 2020 and 2026 on Islamic fintech, digital finance, artificial intelligence, algorithmic fairness, Sharia compliance, and Maqāṣid al-Sharīʿah. The findings indicate that digital inclusion serves as an entry point for expanding access to financing, investment, and Islamic social finance, particularly for micro, small, and medium-sized enterprises and underserved communities. However, digital access alone is insufficient without transparent, accountable, and auditable Sharia governance. The adoption of artificial intelligence, alternative data, and credit scoring offers opportunities to enhance efficiency, yet it also raises risks of bias, new forms of exclusion, and opacity in algorithmic decision-making. Maqāṣid al-Sharīʿah functions as an evaluative framework for safeguarding wealth, intellect, justice, and public welfare. This study underscores the need for Sharia-based algorithmic auditing in the digital economy and offers a conceptual map for strengthening regulation, consumer protection, and sustainable, inclusive Islamic fintech innovation.